2009
DOI: 10.1002/rra.1236
|View full text |Cite
|
Sign up to set email alerts
|

A model‐based analysis of meander restoration

Abstract: Meander reconnection is becoming a widely applied river restoration measure, aiming to enhance the ecological status of river systems. Based on a physical model study and a 3D hydrodynamic-numerical simulation, the effects of different forms of meander reconnections on flow dynamics, water level and river morphology are investigated in present study including retention of the old main channel for flood protection when the bankfull discharge is exceeded. The distribution of total discharge between the reconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In order to study variability in particle paths, the Monte–Carlo simulation methodology is applied: for every tracer release point in a defined control volume, a large number of particle paths are calculated. The approach was successfully applied in a field study (Tritthart et al ., ) and in a laboratory experiment (Krapesch et al ., ). The simulated paths showed mutual agreement to the observed data in both cases.…”
Section: Methodsmentioning
confidence: 99%
“…In order to study variability in particle paths, the Monte–Carlo simulation methodology is applied: for every tracer release point in a defined control volume, a large number of particle paths are calculated. The approach was successfully applied in a field study (Tritthart et al ., ) and in a laboratory experiment (Krapesch et al ., ). The simulated paths showed mutual agreement to the observed data in both cases.…”
Section: Methodsmentioning
confidence: 99%
“…Tracking methods using Radio Frequency Identification (RFID) transponders have become common in the research community due to their advantages over other tracking technologies in terms of individualized particle displacement information, low cost, battery-free nature and robust design [44][45][46][47][48][49][50][51]. Sediment tracking has been used to assess some restoration projects [52][53][54] but its potential for testable hypotheses to assess restoration outcomes has yet to be fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure is repeated until a pressure equilibrium, that is, a relative pressure of zero, is obtained for every cell at the water surface during the solution cycle of the Reynolds‐averaged Navier–Stokes equations. Previous studies (e.g., Tritthart, Liedermann, & Habersack, ; Krapesch, Tritthart, & Habersack, ; Tritthart, Liedermann, et al, ; Glock et al, ; Glas, Glock, Tritthart, Liedermann, & Habersack, ; Haimann et al, ) have shown good performance of the model RSim‐3D particularly in river applications with associated ecological or sediment‐related research questions.…”
Section: Methodsmentioning
confidence: 93%